KOLERASI ANTARA DUKUNGAN INFRASTRUKTUR DAN OPTIMALISASI HUKUM DI INDONESIA - Rahmad, Noor; Shinta Oliviyana Anggita (Universitas Tabanan, 2025)
Law enforcement is a fundamental component in realizing the ideal of a rule of law state, as mandated by Article 1 paragraph (3) of the 1945 Constitution of Indonesia. However, the legal effectiveness of law enforcement is not solely determined by legal norms or the performance of law enforcement officers. It is also strongly influenced by the adequacy of facilities and infrastructure that support the entire enforcement process. This study aims to examine how such facilities and infrastructure affect the effectiveness of law enforcement in Indonesia and to evaluate the government’s efforts in strengthening the national legal infrastructure. Using a qualitative method with a literature study approach, the research draws on law books, legislation, and academic journals related to public policy and law enforcement. The findings reveal that limited facilities and infrastructure contribute to delays in investigations, unequal access to justice particularly in remote areas and the suboptimal use of digital technology. Although the government has introduced innovations such as e-court, e-prosecution, and e-policing, their implementation remains inconsistent across regions. Therefore, a comprehensive national strategy is required to develop an integrated and modern legal infrastructure capable of supporting justice, certainty, and the overall effectiveness of law enforcement.